The economic burden of rotavirus hospitalization among children < 5 years of age in selected hospitals in Bangladesh. Issue 48 (26th November 2021) - Ahmed, Sayem; Dorin, Farzana; Satter, Syed Moinuddin; Sarker, Abdur Razzaque; Sultana, Marufa; Gastanaduy, Paul A; Parashar, Umesh; Tate, Jacqueline E.; Heffelfinger, James D.; Gurley, Emily S.; Khan, Jahangir A.M.
Abstract: Background: Rotavirus is a common cause of severe acute gastroenteritis among young children. Estimation of the economic burden would provide informed decision about investment on prevention strategies (e.g., vaccine and/or behavior change), which has been a potential policy discussion in Bangladesh for several years. Methods: We estimated the societal costs of children <5 years for hospitalization from rotavirus gastroenteritis (RVGE) and incidences of catastrophic health expenditure. A total of 360 children with stool specimens positive for rotavirus were included in this study from 6 tertiary hospitals (3 public and 3 private). We interviewed the caregiver of the patient and hospital staff to collect cost from patient and health facility perspectives. We estimated the economic cost considering 2015 as the reference year. Results: The total societal per-patient costs to treat RVGE in the public hospital were 126 USD (95% CI: 116–136) and total household costs were 161 USD (95% CI: 145–177) in private facilities. Direct costs constituted 38.1% of total household costs. The out-of-pocket payments for RVGE hospitalization was 23% of monthly income and 76% of households faced catastrophic healthcare expenditures due to this expense. The estimated total annual household treatment cost for the country was 10 million USD. Conclusions: A substantial economic burden of RVGE in Bangladesh was observed in this study. Any prevention of RVGE through cost-effective vaccination or/and behavioural change would contribute to substantial economic benefits to Bangladesh.